Prevalencia de caries dental y su relación con la dieta e higiene bucal de jóvenes conscriptos del grupo de Caballería Mecanizada nro.18 Cazadores de los Ríos”, período octubre 2019 – marzo 2020 - Martínez Guaicha, María José (2020)
The prevalence of dental caries on many occasions is directly related to the consumption of certain cariogenic foods and poor or deficient oral hygiene. That is why the purpose of this research was to determine the prevalence of dental caries and its relationship with the diet and oral hygiene of young conscripts of the mechanized cavalry group No. 18 "Cazadores de los Ríos", for which a descriptive, quantitative and cross-sectional study was carried out. The sample consisted of 37 young people between the ages of 18 and 25 who underwent an oral examination to determine the prevalence of caries and the level of oral hygiene using the IHOS index and a survey. In addition, to determine the cariogenic food groups that they consume most frequently, they filled out a food diary. The results showed a high prevalence of caries with 81.1%. The cariogenic risk of the diet was 45.9% moderate and 24.3% high. In addition, the level of oral hygiene is regular in 51.4% and bad in 18.9%, which is influenced by a poor brushing frequency and technique and the decreased use of hygiene accessories such as dental floss. Finally, it is concluded that between the 3 variables analyzed there is a statistically significant relationship. Key Words: Military, sucrose, cariogenic agents, biofilm, streptococcus